Pengembangan Kemampuan Pengolahan Dokumen melalui Microsoft Word pada Siswa AKL SMKS Dewantara Sumbang - Fajar Tri Junianto (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The advancement of information and technology requires various fields to master knowledge in the field of information technology to face this era of globalization. Information and Communication Technology has developed in all fields. Therefore, the use of communication technology devices needs to be taught in all education. Microsoft Word is a reliable word processing application and is widely used by computer users. So the Microsoft Word application provides enormous benefits for the world of technology that continues to develop, in this case word processing is used for productive activities, education and various other things that require a reliable word processing application. This community service activity aims to provide Microsoft Word socialization and training to class X AKL students of SMKS Dewantara Sumbang. The evaluation results show a significant increase in the cognitive understanding and basic skills of participants, with achievements of up to 75%. This shows that the training process is running well and has a positive impact.